Frequency of Sources of Referral of Child Psychiatric Cases at Hyderabad (Medical Forum Monthly, 2021)
Objective: This study is designed to determine the frequency of sources of referral of child psychiatric cases.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Sir Cowasji Jehangir Institute of Psychiatry (CJIP) and Liaquat University Hospital (LUH), Hyderabad from June 2018 to Feb 2019.Materials and Methods: 175 children with psychiatric problems were included in this study. History was taken for the duration of symptoms and the source of referrals was inquired. All information was noted in the proforma.Results: 67.43% (118/175) sources of referral were parents, schoolteachers were responsible for 10.29% (18/175), and doctors for 22.29% (39/175).Conclusion: Mental disorders are among the most burdensome of all classes of disease because of their high prevalence, chronicity, early age of onset, and resulting in serious impairment and disability.